The geopolitical Importance of Afghanistan in India's relations with Central Asia (Salam International Academic Journal, 2019)
The prospect of future Indian international policy in a future-oriented scenario is the transfer of power to the Asian continent and escape from politically driven foreign policy of the state to an economy driven foreign policy. Afghanistan's geopolitical position lies as a decisive factor at the heart of these developments and the future regional equations in the country's foreign policy debate. As an emerging power in the pursuit of regional hegemony and global welfare, one of the areas of interest in India's foreign policy is Central Asia as the closest base for future regional military-economic rivalries, and it is heavily engaged in spending its foreign policy capabilities on expanding the sphere of regional influence in Central Asian countries, particularly Uzbekistan. The geopolitical position of Afghanistan serves as a catalyst in realization of foreign policy goals of India and Central Asian states. This article is a clearer account of the prospect of India's relations with Central Asian countries, with more emphasis on Uzbekistan, and the importance of the geopolitical position of Afghanistan in these developments. And at the end of the article, the author's main idea of the topic of importance of the geopolitical position of Afghanistan in India's relations with Central Asia has been proven and highlighted.